Pengaruh Konsentrasi Ekstrak Etanol Daun Pepaya (Carica Papaya L) Terhadap Kematian Larva Nyamuk Aedes Aegypti - Adnyani, I Gusti Ayu Prapti; Sudarmaja, I Made (E-Jurnal Medika Udayana; Vol 6 No 11 (2017): E-Jurnal Medika Udayana, 2017)
This study aims to determine the effect of the concentration of ethanol extract of leaves of papaya against the Aedes aegypti mosquito larvae mortality. The design of this study is purely experimental with randomizesd post test only control group design. The sample used is Aedes aegypti larvae as much as 150 animals. The independent variable in this study is the concentration of the ethanol extract of papaya leaf, the dependent variable is the death of Aedes aegypti larvae. Data were analyzed by One Way Anova followed by Post Hoc test. At a concentration of 1% after observation for 24 hours, the average number of Aedes aegypti larvae mortality is 100%. One Way Anova obtain results, which means that there is a statistically significant difference in mortality between groups Aedes aegypti larvae were studied (p <0,05). Post hoc analysis results to obtain the results are significant differences in mortality between the concentrations of 0% and 0,125%, 0% and 0,25%, 0% and 0,5%, 0% and 1%, and 0,0625% and 1%, but there is no significant difference in mortality between the concentration of 0,0625 compared with controls. Based on the results of the analysis that there are significant concentrations of ethanol extract of the leaves of the death of Aedes aegypti larvae. All concentrations of ethanol extract of papaya can cause the death of larvae of Aedes aegypti, with the highest number of deaths at a concentration of 1%. Keyword : papaya leaves, larvae, dengue hemorhagic fever.